Argent: A web based augmented reality framework for dynamic content generation - Kurt, Gökhan (Institute of Science and Technology, 2020)
In the modern world, people are more and more interested in interactive technologies. Education, research and business habits are effected by this change and humans can be more efficient using interactive technologies. Augmented reality (AR), which is a novel addition to those interactive technologies, is especially effective in this matter. Through augmented reality, people can immerse more deeply with the subject experience and they can have enhanced interaction. Despite the usefulness of augmented reality, it may not always be efficient develop an AR application in terms of development cost. AR development still requires knowledge and experience with certain tools and frameworks. Such tools are usually programming and game development tools and they require programming and technical skills that is gained by long-term education and training. People experienced in design and content creation can be deprived of the ability to create and maintain AR applications. Nowadays, tools like Unity, Vuforia, ARKit and ARCore provide ways to develop AR applications without the need to have knowledge of low-level calculation and programming that is required for AR technology. Normally, developing an AR application would have taken years of research and development by large teams, but thanks to SDK and APIs provided by these tools, AR applications can be developed by small development teams easily and quickly. However, AR is still not easily accessible by all the tech-savvy people that may be interested in developing such applications. Majority of AR applications are developed using Unity. There are visual programming solutions in Unity, but they are not suitable to be used in AR applications. A Unity-based tool that allows people without programming skills to create AR applications, will be utmost useful. Such a tool would require features such as, creating an application without programming, optional support to do programming and scripting, real time updates and ability to ship without any build and packaging step, support for 3D object, image and video, the ability to modify objects and preview them in real time, and the ability to create user interfaces. The tool should also have a user friendly interface and experience. It should introduce the innovative features without changing the conventional workflows. Existing tools do not provide these features which are crucial for an ordinary person to create AR applications.
Argent: Web tabanlı dinamik içerik destekli artırılmış gerçeklik geliştirme altyapısı
Thesis (M.Sc.) -- İstanbul Technical University, Institute of Science and Technology, 2020
Keywords: ARgent Framework; architecture of ARgent Framework